2019
DOI: 10.1002/maco.201910873
|View full text |Cite
|
Sign up to set email alerts
|

Development of microbially influenced corrosion on carbon steel in a simulated water injection system

Abstract: Microbially influenced corrosion (MIC) on internal pipeline surfaces has become a severe problem during the water injection process in secondary oil recovery. The formation of a biofilm, normally dominated by sulfate-reducing bacteria (SRB), is believed to be the critical step of the MIC process. A continuously fed biofilm simulating the water injection process was operated to investigate the influence of biofilm development on MIC behavior in the early phase of corrosion development. The development of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[ 8 ] Therefore, marine engineering steels are required to possess both corrosion‐resistant and antifouling properties. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Therefore, marine engineering steels are required to possess both corrosion‐resistant and antifouling properties. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Both pitting depth plots (Figure 6-3g) and pitting corrosion rate diagrams (Figure 6-3h)showed that the pitting corrosion accelerated from Day 326 in Control, which indicated that microbes tended to attack subtle areas that were previously corroded on the metal surface. As shown in our previous study, a dense and compact biofilm formed on the coupon surface could be a barrier for the transfer of carbon substrates from the bulk liquid phase to deep layers of the biofilm(Zhong et al 2019). The diffusion limitation likely caused low carbon concentrations at the bottom of the biofilm (i.e.…”
mentioning
confidence: 58%
“…First of all, H2S produced by SRB could directly interact with iron, inducing the anodic reaction of iron dissolution (Bai et al 2015). SRB could also extract electrons directly from Fe 0 , especially when associated with low carbon levels, which would cause pitting corrosion underneath the biofilm (Gu et al 2009, Zhong et al 2019. Further, the metal acts as an electrode submerged in the electrolyte, thus the corrosion process is also influenced by many other ions, such as chloride, in the medium.…”
Section: Introductionmentioning
confidence: 99%